(untitled) (Journal of Economic Research & Business Administration, 2018)
This article aims to study world experience of entrepreneurial universities and reveal main barriers to the development of entrepreneurial education in Kazakhstan. The study was carried out using secondary data, in particular global university entrepreneurship reports, scientific articles of local and foreign scientists, and legislative acts. World experience shows that entrepreneurial universities more fully meet innovation needs of the economy and business in the field of education, being educational, research and industrial centers. Results of this study reveal that for successful development of entrepreneurial university it is important to create mechanisms of transformation of classical education, and take measures for creating favorable external and internal conditions to ensure the strategic interaction in the system “University-Business-Government”. Regardless of the approaches applied in different countries, entrepreneurship is recognized as the most important area of education.